Investment benefits of cross sectors diversification on two boards of Bursa Malaysia / Surianor Kamaralzaman, Mohd Jais Atan and Ahmad Bukhari Mohd Yasin - Kamaralzaman, Surianor; Atan, Mohd Jais; Mohd Yasin, Ahmad Bukhari (2005)
The purpose of this study is to determine · the prospects of cross sectors diversifications of selected stock price movement listed on the Main and Second Board on the Bursa Malaysia. This is basically to see the cross sectors diversification based on the return portfolios, coefficient of variation and standard deviation of the chosen stocks. The data consists of monthly closing prices of the top forty (40) stocks based on the market capitalization as at the beginning of 1998 over a 6 year period from January 1998 to December 2003 on the two boards of Bursa-Malaysia. From the results, based on the return portfolio, it shows that all the twenty (20) stocks of Main Board have good performance if combined with MYINFO from Second Board. According to the coefficient of variation, mostly Main Board stocks have good combination with the CREST from the Second Board. Besides, according to cross diversification based on the standard deviation, shows that most Main Board stocks have good combination with TOYOCEM from the Second Board. The cross sectors diversification exhibit significantly low positive correlations between forty sectors under investigation. The positive correlations impede the process of risk reduction, which is the main trust of portfolio diversification as proposed by Markowitz. While the finding of an alternative investment strategy is beyond the scope of this paper, it is worth considering investing based on international diversification.' The high growth sector, particularly those listed on the newly formed Malaysian Exchange of Securities Dealing & Automated Quotation Bhd. (MESDAQ), promises potentially higher returns that should be cushioned against probable high risk.